Structural Design and Analysis for a Timber-Concrete Hybrid Building - Zhang, Xiaoyue; Xuan, Lu; Huang, Wanru; Yuan, Lin; Li, Pengcheng (Frontiers in Materials, 2022)
The benefits of using wood in tall and commercial construction are undisputed, namely reducing the carbon footprint, shortening construction times, and enhancing seismic and building physics performance. The international market for wood as a structural material in tall and non-residential construction, however, is still relatively untapped. China is home to the world’s largest population and the largest construction sector worldwide, yet wood-products are only used in a small fraction of buildings. The main reasons of this situation are the fire regulations and lack of guidelines for novel wood-based structural systems. This paper describes the design of a 10-storey timber-concrete business hotel which will be erected in the Guizhou province of China. The foundation design, gravity system design, lateral load resisting system design, seismic analysis and the fire resistance design were conducted, and the procedure provided appropriate information to the technological feasibility to promote the development of timber-based hybrid high-rise construction systems in China.